ASSESSMENT OF ORGANISATIONAL LEADERSHIP FOR KNOWLEDGE MANAGEMENT PRACTICE IN THE NIGERIAN CONSTRUCTION INDUSTRY - Kulomri Jipato ADOGBO; Baba Adama KOLO; Kene Christopher Lawrence NZEKWE (Journal of Construction Project Management and Innovation)
The Nigerian construction industry (NCI) is described as being slow to innovate and lacking the capacity to deliver its services and products adequately. However, studies have continued to suggest ways of improving service delivery in the industry. One such way is for the NCI to adopt concepts of knowledge management (KM) to improve service delivery. The aim of this study is to assess organisational leadership for the adoption of KM practice in the NCI. The objectives of the study are to identify the attributes of leadership behaviours and KM; to establish the leadership behaviours exhibited by consulting firms in the NCI, and to establish whether the consulting firms in the NCI exhibit KM. The instrument used for data collection in this study was a structured questionnaire. The instrument was administered on senior management staff of consulting firms in the NCI. The number of questionnaires completed and returned were 110 which represented 45.9 per cent of the total questionnaires administered (240). The data collected were analysed in the form of descriptive statistics to achieve the study objectives. The findings of the study showed that of the three leadership behaviours, the firms surveyed exhibit transformational leadership behaviours more than the transactional and laissez-faire leadership behaviours. Also, the results also showed that the most prevalent KM behaviours exhibited by firms is ‘information technology’ and the least exhibited is ‘strategy’. The existence of the transformational leadership behaviour and prevalence of KM behaviours suggests that there is a basis for the development of a framework for the adoption of KM practice by firms in the NCI. It is recommended that consulting firms formally adopt KM practice to improve their competitiveness in the market place and the quality of their service delivery in the NCI.